Is everything Fair in Marketing?(unravelling the Knitty-gritty of Ambush Marketing with Special Reference to India) - Tripathi, Aditya Prakash (Indian Journal of Marketing, 2007)
The problem of ambush marketing has been plaguing the organizers of various sporting and other events for the last four to five years. Due to the enormous financial losses caused by ambush marketing, the sponsors have been reconsidering the decisions to shell out astronomical sums for sponsoring various events. This paper analyses in great detail the concept of ambush marketing to its genesis, the various famous incidents of ambush marketing in Indian scenario and evaluates the existing Legal framework in combating this menace. It also tries to come up with the suggestions to combat ambush marketing and also tries to cull out a suitable anti-ambush marketing legislative policy for the Indian scenario.